Pathogen-Mediated Assembly of Plant-Beneficial Bacteria to Alleviate Fusarium Wilt in Pseudostellaria heterophylla - Yuan, Qing-Song; Wang, Lu; Wang, Hui; Wang, Xiaoai; Jiang, Weike; Ou, Xiaohong; Xiao, Chenghong; Gao, Yanping; Xu, Jiao; Yang, Ye; Cui, Xiuming; Guo, Lanping; et al. (Frontiers in Microbiology, 2022)
Fusarium wilt (FW) is a primary replant disease that affects Pseudostellaria heterophylla (Tai Zi Shen) and is caused by Fusarium oxysporum, which occurs widely in China under the continuous monocropping regime. However, the ternary interactions among the soil microbiota, Taizishen, and F. oxysporum remain unknown. We investigated the potential mechanism by which the pathogen-mediated Taizishen regulates the soil and the tuberous root microbiota. We analyzed the regulation of the microbiome by pathogen-mediated Taizishen via high-throughput sequencing. Plant-pathogen interaction assays were conducted to measure the arrival of F. oxysporum and Pseudomonas poae at the tuberous root via qPCR and subsequent seedling disease incidence. A growth assay was used to determine the effect of the tuberous root crude exudate inoculated with the pathogen on P. poae. We observed that F. oxysporum-mediated Taizishen altered the diversity and the composition of the microbial communities in its rhizosphere soil and tuberous root. Beneficial microbe P. poae and pathogen F. oxysporum were significantly enriched in rhizosphere soil and within the tuberous root in the FW group with high severity. In addition, interaction network analysis showed that accompanied with FW incidence, P. poae co-occurred with F. oxysporum. Furthermore, the aqueous extract of Taizishen tuberous root infected by F. oxysporum substantially promoted the growth of P. poae isolates (H1-3-A7, H2-3-B7, H4-3-C1, and N3-3-C4). These results indicated that the extracts from the tuberous root of Taizishen inoculated with F. oxysporum might attract P. poae and promote its growth. The colonization assay showed that F. oxysporum promoted the colonization of P. poae on the tuberous root. A pathogen-induced attraction assay further showed that Taizishen assembled P. poae via F. oxysporum mediation. Our data suggest that pathogen-mediated Taizishen promoted and assembled plant-beneficial microbes against plant disease. Therefore, deciphering the beneficial associations between pathogen-mediated Taizishen and microbes can provide novel insights into the implementation and design of disease management strategies.